PENDAMPINGAN KEPEMIMPINAN KEPALA RA SEBAGAI TELADAN DALAM MENINGKATKAN PROFESIONALISME PENDIDIK - Rina Mida Hayati; Ferdian Utama; Muhammad Yusuf; Yuning Eka Rahma Wati; Sunarto Sunarto; Muhamad Rudi Wijaya; Badarudin Badarudin (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2026)
This community service activity aims to improve the professionalism of educators through exemplary-based leadership assistance for the head of RA. The method used is Participatory Action Research (PAR) with stages of planning, action, observation, and reflection involving the active participation of the head of RA and educators. Mentoring activities are carried out through Islamic leadership workshops, academic supervision training, and exemplary practices in daily activities. The results of the activity showed an increase in the understanding and leadership practices of the head of RA that were more open, communicative, and coaching-oriented, as well as an increase in the professionalism of educators in learning planning, classroom management, the use of varied learning methods, and the integration of Islamic values. In addition, there has been a change in a more collaborative and professional work culture in the RA environment. Exemplary leadership assistance for RA heads has proven to be effective in improving the professionalism of educators and the quality of early childhood education services in a sustainable manner.